Improvement of Theme 3 Subtema 4 Learning Results Through Audio Visual Media in Class 1 Students of SDN Karangwangkal - Widya Kurniawati (Universitas Sebelas Maret, 2020)
This research is a classroom action research (PTK) which consists of two cycles. This PTK has two cycles in one cycle, there are four stages, namely Plan, ACT and observer, reflect. The research subjects were grade I students of SDN Karangwangkal Banyumas, Central Java, with 26 students. Data collection techniques using test and non-test techniques. As for the assessment instrument using item items and observation of the scoring rubric. Analysis of the data used in the study included a comparative descriptive technique, namely a statistical technique by comparing the scores between cycles, the mean, the minimum score, the maximum, and the percentage. The results of the study that the use of audio-visual media can improve student learning outcomes in Theme 3 Sub-theme 4 Class 1 Night Activities of SDN Karangwangkal, this is evidenced by the learning outcomes in cycle I, namely 10 students out of 26 students or 38% who have not completed yet. students who complete as many as 16 students from 26 students or 62%. In cycle II, there were 3 out of 26 students or 12% of the students who had not completed, while 23 students out of 26 students or 88% who had finished. This means that student learning outcomes increase from cycle I to cycle II. The conclusion of this study is that using audio-visual media can improve student learning outcomes in Theme 3 Sub-theme 4 Class 1 Night Activities of SDN Karangwangkal.